2018
DOI: 10.1039/c7cp08249e
|View full text |Cite
|
Sign up to set email alerts
|

When is electronic friction reliable for dynamics at a molecule–metal interface?

Abstract: We investigate rates of electron transfer for generalized Anderson-Holstein models in the limit of weak molecule-metal coupling, using both surface hopping and electronic friction dynamics in one and two dimensions. Overall, provided there is an external source of friction, electronic friction can sometimes perform well even in the limit of small metal-molecule coupling and capture nonadiabatic effects. However, we show that electronic friction dynamics is likely to fail if there is a competition between noneq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…When the Massey parameter approaches 1, any method that does not incorporate several possible paths will be unable to properly model the dynamics. This result is consistent with that of Coffman and Subotnik 25 , where it has been concluded that a friction approach seems to fail in the case where there are nonequivalent pathways. Such behavior can be explained by the breakdown of the underlining EH theory as opposed to an intrinsic failure of the friction approach.…”
Section: Discussionsupporting
confidence: 92%
“…When the Massey parameter approaches 1, any method that does not incorporate several possible paths will be unable to properly model the dynamics. This result is consistent with that of Coffman and Subotnik 25 , where it has been concluded that a friction approach seems to fail in the case where there are nonequivalent pathways. Such behavior can be explained by the breakdown of the underlining EH theory as opposed to an intrinsic failure of the friction approach.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, how do we know when the weak-coupling limit is satisfied and when the MDEF method is reliable for a particular system? While this question was partially addressed by Dou and Subotnik for simple model systems, 29 here we provide quantitative insights for state-to-state scattering of NO from Au(111), which has been considered a representative strong-coupling showcase for the breakdown of electronic friction theory. 30 , 31 …”
Section: Introductionmentioning
confidence: 88%
“…In practice, the MDEF method is always further approximated by imposing the Markov approximation of instantaneous response in the constant coupling limit, where some pragmatic assumptions are made in how the friction tensor is calculated from DFT in that limit . Examples of approximations include the local density friction approximation (LDFA), which allows for an efficient calculation of scalar isotropic friction from the electron density of the metal ,− and the more realistic orbital-dependent friction (ODF), , which is calculated from Kohn–Sham DFT via time-dependent perturbation theory to provide a better description of the mode-selective nature of nonadiabatic molecule-metal energy transfer. …”
Section: Introductionmentioning
confidence: 99%
“…The electronic friction tensor lies at the core of the definition of the friction force in MDEF and can be understood as a first order correction to the Born-Oppenheimer approximation in the presence of a manifold of fast relaxing electronic states 16 . As a consequence, MDEF is expected to break down when strong non-adiabatic effects are present 1,17 and in cases where charge a) Electronic mail: yairlitman@gmail.com b) Electronic mail: mariana.rossi@mpsd.mpg.de transfer mechanisms are dominant 11 . Despite these shortcomings, MDEF has proven to be a useful approach for several realistic systems and conditions, in which high-level simulations can explain well-controlled experiments 6,9,[18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%